Histopathological Studies of the Liver and Kidney in Mice Fed on Smut Wheat Infected with Tilletia - Al-Taie, Mustaffa A K; Faraj, Mohammed K (Al-Nahrain Journal of Science, 2018)
The current study was designed to investigate the effect of Tilletia smut spores on histopathological changes in liver and kidney in mice. Twenty animals were divided into two equal groups, 10 mice each, control group fed on normal diet and the treated groups were fed on a mixture of 50% normal diet with 50% wheat infected with Tilletia for 30 days. Histopathological sections taken from liver and kidney treated with Tilletia revealed several alterations. The changes in liver included, multiple granulomatous lesions, area of coagulation necrosis, vacuolar degeneration in the cytoplasm of hepatocytes, proliferation of hepatocytes with formation of pseudolobull which initiates for procancer. Whereas in the kidney, the changes included cellular degeneration, thickness of Bowman's capsules, in other section aggregation of inflammatory cells in the interstitial tissue together with degeneration and sloughing of epithelial lining of the renal tubules.